High Performance Thin Layer Chromatographic Estimation of Simvastatin in Bulk and Tablet Dosage Form - LAKSHMANA RAO*, A.; SUNEETHA†, D. (Asian Journal of Chemistry, 2024)
A simple, fast, specific, accurate and precise HPTLC method has been developed and validated for the estimation of simvastatin in pure and in tablet dosage forms. Aluminium backed silica gel 60F254 were used as stationary phase and a mixture of toluene:ethyl acetate:formic acid in the ratio 5:1.5:0.5 v/v/v were used as mobile phase. Densitometric analysis was carried out in absorbance mode at 242 nm. The Rf value of simvastatin was found to be 0.26 ± 0.01. The method was validated in terms of linearity, accuracy, precision and recovery. The linearity curve was found to be linear over 200-1000 ng per spot. The limit of detection and limit of quantification were found to be 50 and 160 ng per spot, respectively. The proposed method can be useful for estimation of simvastatin in the quality control of bulk and tablet dosage forms.